Vancomycin-associated linear IgA disease mimicking toxic epidermal necrolysis - Amanda Regio Pereira; Luis Henrique Barbizan de Moura; Jhonatan Rafael Siqueira Pinheiro; Victor Pavan Pasin; Milvia Maria Simões e Silva Enokihara; Adriana Maria Porro (Sociedade Brasileira de Dermatologia, 2016)
Abstract Linear IgA dermatosis is a rare subepidermal autoimmune blistering disease characterized by linear deposition of IgA along the basement membrane zone. In the last three decades, many different drugs have been associated with the drug-induced form of the disease, especially vancomycin. We report a case of vancomycin-induced linear IgA disease mimicking toxic epidermal necrolysis. The aim of this work is to emphasize the need to include this differential diagnosis in cases of epidermal detachment and to review the literature on the subject and this specific clinical presentation.